2015
DOI: 10.1007/s10562-015-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Recyclability Improvement Through Adjusting the Tethering Strategy for Pd-Catalyzed Suzuki–Miyaura Coupling Reaction of Aryl Chlorides

Abstract: Four mesoporous SBA-15-immobilized Nheterocyclic carbene (NHC) palladium catalysts with different nitrogen ligands were synthesized. The activity and recyclability of the catalysts were investigated in SuzukiMiyaura cross-coupling reaction of typical aryl chlorides and arylboronic acids. Bulky NHC moiety was essential for efficiency, while tethering of nitrogen ligands on both support and NHC group could dramatically improve recyclability of the catalysts. The strategy offers an alternative strategy for design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Originating from the use of (C^C)-chelating biscarbene palladium complexes in the Mizoroki–Heck reaction, we investigated a related series of (C^N)-chelating NHC palladium complexes (Figure ). Several other palladium-containing cations of the latter type comprising the pyrimidyl moiety were reported . We found that, for small substituents at the NHC ligands (e.g., those substituted by a methyl group), two ligands are bound at a cationic palladium center, accompanied by a [Pd­(DMSO)­Cl 3 ] counterion ( 1 , Figure ).…”
Section: Introductionmentioning
confidence: 60%
“…Originating from the use of (C^C)-chelating biscarbene palladium complexes in the Mizoroki–Heck reaction, we investigated a related series of (C^N)-chelating NHC palladium complexes (Figure ). Several other palladium-containing cations of the latter type comprising the pyrimidyl moiety were reported . We found that, for small substituents at the NHC ligands (e.g., those substituted by a methyl group), two ligands are bound at a cationic palladium center, accompanied by a [Pd­(DMSO)­Cl 3 ] counterion ( 1 , Figure ).…”
Section: Introductionmentioning
confidence: 60%
“…The imidazolium salts 92 – 93 were initially prepared by direct quaternization of 2,6-bis­(bromomethyl)­pyridine with 0.67 equiv of the corresponding N-substituted imidazoles in acetone under reflux for 16–18 h . Addition of 93 to the respective N -alkyl-3-(trialkoxysilyl)­propan-1-amine in the presence of a base finally yielded the trialkoxysilyl functionalized NHC precursors 94 – 96 in quantitative yields. , Likewise, pyrrolidine derived trialkoxysilanes were also used with 92 – 93 to synthesize the trialkoxysilyl functionalized NHC precursors 97 – 99 in good yields (70–75%). , Later, the same group employed a similar synthetic strategy to prepare the dioxolane-modified asymmetrical and chiral NHC precursors 102 – 103 , which were then used for the preparation of immobilized chiral Au, Rh, and Pd NHC complexes. , However, in contrast to the syntheses of 97 – 99 , which had long reaction times at room temperature, the alkylation step of the syntheses of 102 – 103 was conducted under microwave irradiation in only 3 h, obtaining the products in quantitative yields. Furthermore, Jia et al .…”
Section: Synthetic Strategies For the Immobilization Of N-heterocycli...mentioning
confidence: 99%
“…As listed in Table , the SBA-15 supported NHC compounds 354 – 368 were obtained by grafting the corresponding NHC compounds 56 , 57 , 76 , 105 , 274 , and 323 – 330 onto SBA-15 type supports (Figure ). ,,,, The SBA-15 supports used in those cases were mainly prepared by literature methods. Some were pretreated with trimethylsilyl chloride before removal of the template reagent, deactivating the silanol groups on the outer surface. ,, Additionally, for most supported compounds decreased surface areas and pore sizes were reported compared to the original SBA-15 supports. ,,,, Furthermore, most of the SBA-15 supported compounds were synthesized by heating or reflux in toluene.…”
Section: Synthetic Strategies For the Immobilization Of N-heterocycli...mentioning
confidence: 99%
See 1 more Smart Citation
“…With this context and our former experience on modification of mesoporous silica materials [34][35][36], we herein report the preparation of a series of highly selective Pb(II) ion-imprinted mesoporous silica materials (Pb-IIMS) for separation of Pb(II).…”
Section: Introductionmentioning
confidence: 99%